The creation of music therapy for stress, using different style of piano playing analysis - Zou, Jingjing; Phokha, Pramote (Edelweiss Applied Science and Technology, 2025)
This study explores the therapeutic potential of piano music for alleviating depression and stress, emphasizing the importance of personalized compositions in enhancing emotional well-being. Depression, a prevalent mental health condition, significantly impacts individuals’ daily lives. While traditional treatments like medication and psychotherapy remain crucial, non-invasive approaches such as music therapy offer complementary benefits. Three original piano compositions were created to evoke distinct emotional responses—liveliness, passion, and soothing calmness. Professional evaluations from medical experts highlighted the therapeutic effects of these compositions, with the third piece, characterized by its tranquil rhythm, receiving the highest satisfaction. The findings demonstrate that piano music can activate positive emotions, reduce psychological stress, and foster relaxation, providing a unique emotional outlet for individuals experiencing depression. This study underscores the importance of tailoring music therapy to individual preferences and emotional needs. Moreover, integrating piano music into mental health interventions could enhance traditional therapeutic methods. Recommendations include further research on evidence-based applications of music therapy, training programs for therapists, and collaborative efforts between music professionals and mental health practitioners. By leveraging the emotional and psychological benefits of piano music, this approach offers a promising supplementary treatment for improving mental health outcomes.